Navigating the Digital Frontier: EFL Pre-Service Teachers’ Journey in Creating Digital Comic - Syukri, Suhartini; Kurniawan, Muhammad Hari (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The necessity of learning through engagement using digital comic in the EFL context becomes increasingly challenging for EFL pre-service teachers. This study investigates the experiences of 47 EFL pre-service teachers from an Islamic higher education institution in Kendari, Indonesia, in designing digital comics as a learning platform. Using a case study approach, data were collected through reflective journals and a focused group discussion after a 5-week design process. Findings show most participants held positive attitudes toward digital comics, gaining skills in using applications and websites for learning. However, they faced challenges related to technology, self-regulation, design, and pedagogy. The study highlights the effectiveness of consultation sessions and recommends incorporating digital comics into foreign language teaching media courses. This study suggests the integration of technology-oriented platforms like digital comics across all educational levels to enhance engagement and move beyond traditional teaching materials.